DEVELOPMENT OF CANVA-BASED MEDIA FOR JAMBI CULTURE AND LOCAL WISDOM TO BIPA STUDENTS - Rahmawati, Sophia; Bambang, Siti Enik Mukhoiyaroh; Wardani, Diah Octavia Kusuma; Putri, Ratumas Aisyah; Suhesti, Herni (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2025)
The integration of local wisdom into digital learning media for Indonesian for Foreign Speakers (BIPA) remains limited, particularly in beginner-level instruction. Foreign learners require visual and interactive media to understand cultural values, social practices, and regional traditions in a contextual manner. This study aims to develop Canva-based digital learning media that integrates Jambi local wisdom to support cultural learning in BIPA classes. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. Seventeen BIPA students at the University of Jambi participated in the product trial. A pretest–posttest design was applied to assess learning improvement, and data were analyzed using the Wilcoxon signed-rank test due to the small sample size and non-normal data distribution. The results indicate a statistically significant improvement in students’ learning outcomes (p = 0.001) with a large effect size (r = 0.833). Although the limited number of participants limits generalization, the findings demonstrate that Canva-based digital media effectively enhance cultural understanding and learning engagement in BIPA instruction. This study contributes to BIPA pedagogy by offering a practical model for integrating local wisdom into digital language learning media.